Reduction of blood C-reactive protein concentration complements the resolution of sputum bacillary load in patients on anti-tuberculosis therapy - Azam, Khalide; Khosa, Celso; Viegas, Sofia; Massango, Isabel; Bhatt, Nilesh; Jani, Ilesh; Heinrich, Norbert; Hoelscher, Michael; Gillespie, Stephen H.; Rachow, Andrea; Sabiiti, Wilber (Frontiers in Immunology, 2022)
Background: Tuberculosis (TB) is a difficult to treat disease requiring combination of four antibiotics for a minimum of six months. We assessed the relationship of TB bacillary load and CRP as biomarkers of treatment response. Methods: Xpert MTB/RIF-confirmed pulmonary TB cases were enrolled for treatment response assessment in Mozambique. Treatment response was measured using Tuberculosis Molecular Bacterial Load Assay (TB-MBLA) in comparison with standard-of-care Mycobacterium Growth Indicator Tube (MGIT) culture and Blood CRP concentration from baseline to month-6 of treatment. Results: 69 out of the 81 screened presumptive TB cases were enrolled for six-month treatment follow-up resulting in 94% treatment completion rate. Four participants didn’t complete TB treatment and 22 participants had missing CRP or TB-MBLA results and were excluded from TB-MBLA-CRP analysis. Remaining 43 participants with median age of 31 years old (Interquartile range (IQR): 18 – 56), 70% (30/43) male and 70% (30/43) HIV positive were considered for analysis. Culture time-to-positivity and bacillary load were inversely correlated, Spearman’s r= 0.67, p<0.0001. Resolution of sputum bacillary load concurred with reduction of blood CRP, r= 0.70, p<0.0001. At baseline, bacillary load was median (IQR) 6.4 (5.5-7.2) reducing to 2.4 (0.0-2.9) and 0.0 (0.0-0.0) log10CFU/mL at month 2 and six of treatment respectively. Correspondingly, blood CRP reduced from 1.9 (1.6-2.1) at baseline to 1.3 (0.9-1.7) and 0.4 (0.1-0.8) log10mg/dL at month-2 and 6 of treatment. CRP reduction trailed bacteriological resolution at a rate of -0.06 log10 mg/dL compared to bacillary load 0.23 log10 CFU/mL per week. Consequently, 14 (33%) and 37 (88%) of patients had reduced CRP to normal concentration and bacillary load to zero by end of treatment, respectively. Pre-treatment CRP concentration and bacillary load, and resolution during treatment were slightly less in HIV co-infected patients but not significantly different from HIV negative TB patients. Conclusion: TB-MBLA measured bacillary load and blood CRP complement each other in response to anti-TB therapy. Combining both measures can improve the accuracy of these biomarkers for monitoring TB treatment response and shorten turn-around-time since results of both assays could be available in 24 hours.